Pengaruh Persepsi Kebermanfatan dan Persepsi Kemudahan Penggunaan terhadap Minat Menggunakan Layanan Syariah Digital di Pegadaian Syariah Indramayu - Muhammad Qoes Atieq; Mar’atul Azizah (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2021)
ABSTRACT The Digital Sharia Pawnshop application (PSD) is one of the application-based Pawnshop services that helps customers make Sharia Pawn transactions via smartphones, with the Digital Sharia Pawnshop application, it is hoped that it will make it easier for customers to transact. Interest in using Digital Sharia Pawnshops among Sharia Pegadaian customers is still relatively low, therefore the researcher is motivated by the lack of sharia pawnshop customers in the Indramayu branch who have used the Digital Sharia Pawnshop application. The purpose of this study is to determine the effect of perceived usefulness on interest in using Digital Sharia Pawnshop services, to determine the effect of perceived ease of use on interest in using Digital Sharia Pawnshop services, to determine the effect of perceived usefulness and perceived ease of use on interest in using Digital Sharia Pawnshop services. This study was shown to determine whether there is an influence of perceived usefulness and perceived ease of use on interest in using digital sharia services at the sharia pawnshop Indramayu branch. This study uses quantitative methods with a total sample of 95 respondents. Sampling using probability sampling technique with random sampling method. Data collection techniques using questionnaires and documentation. The data analysis techniques used in this study include the research instrument test, classical assumption test, multiple linear regression analysis test, hypothesis testing, and coefficient of determination test. Based on the results of the study, the results of the partial test (t test) indicate that the perceived usefulness of the value of tcount > ttable is 2,636 > 2,028 and a significant value of 0.010 means that there is a significant and significant effect on the interest in using digital sharia pawnshop services, the perception of ease of use is obtained by the value of tcount > ttable, namely 3,474 > 2,028 and a significant value of 0.001 means that it has a significant and significant effect on interest in using digital sharia pawnshop services. The results of the simultaneous test (F test) show that the perceived usefulness and perceived ease of use are obtained by the value of Fcount > Ftable, which is 11.058 > 2.70, meaning that there is a significant and significant effect on interest in using. The R value is 0.193 so it can be seen that the effect of perceived usefulness and perceived ease of use contributes 19.3% to the interest in using digital sharia pawnshop services. Keywords: Perception of Usefulness, Perception of Ease of Use, Service Interest, Sharia Pawnshop Application